Impacts of Covid-19 on telemedicine in Brazil - Maldonado, José; Cruz, Antonio (Cadernos do Desenvolvimento, 2023)
COVID-19 pandemic is an extreme global event with significant impacts on society and the economy. Due to its outbreak and the following social distancing, there has been an intensification of the use of telemedicine, with a debate about technology on global and national levels. The aim of this paper is to identify the main impacts of the novel Coronavirus on the short-term use of telemedicine in Brazil. The evidence shows an increasing acceptance of telemedicine lately, considering the number of assisted patients as well, as public and private initiatives. The pandemic tends to accelerate the commitment of society’s representatives to the proposition of solutions regarding the key issues that have limited its diffusion in the country. How the interests of public health and private health prevail remains open, considering the perspective that science, technology, and innovation should be subordinated to social needs and specifically to the Unified Health System in accordance with a national strategy of development.